Synthesis and Characterization of ZnO Nanoparticles under Different Spray Dryer Processing Parameters and Solution Concentrations - Duman, Şeyma; Özkal, Burak (Akademik Perspektif Derneği, 2019)
In this study, it has been aimed to investigate the effect of different concentrations and spray dryer process parameters on morphology and particle size of ZnO nanoparticles. In the scope of the study ZnO nanoparticles were synthesized from zinc acetate solutions and the structural and morphological characterizations were carried out. Successive spray drying and thermal decomposition processes were performed in order to synthesize of ZnO nanoparticles. The X-ray diffraction analysis revealed single-phase ZnO hexagonal structure. It has been determined that the densities increased while the specific surface area values decreased with increasing of concentration. By the changing of spray dryer process parameters, particle size and density have altered. According to SEM micrographs, it has been observed thatspherical morphologies ofspray dried powders exhibit rod/rodlike morphology with the thermal decomposition process. In the evaluation of results, it has been ascertained that the structural and morphological properties of ZnO nanoparticles varied by concentration and by changing the spray dryer process parameters.

Bu çalışmada ZnO nanopartiküllerinin morfoloji ve partikül boyutu üzerine farklı püskürtmeli kurutucu proses parametrelerinin ve konsantrasyonun etkisinin araştırılması amaçlanmıştır. Çalışma kapsamında çinko asetat çözeltilerinden hareketle ZnO nanopartiküller sentezlenmiş, yapısal ve morfolojik özellikleri incelenmiştir. ZnO nanopartiküllerin sentezlenmesinde püskürtmeli kurutma ve termal bozunma prosesleri ardışık olarak uygulanmıştır. X-ışını kırınım analizi, tek fazlı ZnO altıgen yapısını göstermiştir. Konsantrasyonun artırılması sayesinde sentezlenen tozların yüzey alanı değerleri azalırken gerçek yoğunluk değerlerinin arttığı belirlenmiştir. Ayrıca püskürtmeli kurutucu proses parametrelerinin değiştirilmesi ile partikül boyut ve yoğunluk değerleri değişmiştir. SEM görüntülerine göre; püskürtülerek kurutulmuş tozların küresel morfolojilerinin termal bozunma prosesi ile çubuk/çubuksu morfoloji sergilediği gözlenmiştir. ZnO nanopartiküllerin yapısal ve morfolojik özelliklerinin, püskürtmeli kurutucu proses parametrelerinin ve konsantrasyonun değiştirilmesiyle farklılıklar gösterdiği tespit edilmiştir.
Farklı Püskürtmeli Kurutucu Proses Parametreleri ve Çözelti Konsantrasyonunda ZnO Nanopartiküllerin Sentezlenmesi ve Karakterizasyonu
Keywords: Engineering; Mühendislik